Radioprotection of human lymphoid cells by exogenously supplied glutathione is mediated by gamma-glutamyl transpeptidase. - Jensen, G L (1983)
Human lymphoid cells depleted of glutathione by treatment with buthionine sulfoximine, a specific inhibitor of gamma-glutamylcysteine synthetase, may be partially repleted by adding glutathione in the medium. The mechanism of repletion involves the action of gamma-glutamyl transpeptidase on exogenous glutathione, transport of products of glutathione metabolism, and intracellular synthesis of glutathione. Lymphoid cells, previously shown to export glutathione at rates proportional to intracellular glutathione levels, do not take up intact glutathione to an appreciable extent, even under conditions of marked glutathione deficiency. The role of glutathione in radioprotection was examined by subjecting cells to gamma-radiation after modification of cellular glutathione levels. Glutathione-depleted cells exhibited increased radiosensitivity under aerobic conditions, as compared to the nondepleted controls. Partial repletion of cellular glutathione prior to irradiation led to radiosensitivity comparable to nondepleted controls. Cells were not protected by suspension in media containing glutathione just prior to irradiation; thus, protection appears to require intracellular glutathione.